Sleep quality and diabetes associated factors, effect and interventions - Alghamdi, Razan Adel; Alkanderi, Roaa Ali; Jaafari, Mohammed Ahmed; Shehri, Abdulrahman Mohammed Al; Alqahtani, Haya Ali; Aldawsari, Nasser Ibrahim; Aloqayli, Renad Ibrahim; Baothman, Mohammad Salah; Aldandan, Ahmed Ali; Alfauri, Amani Talal; Alzain, Qasem Abdulmohsen (International Journal Of Community Medicine And Public Health, 2023)
Getting sleep is incredibly important for maintaining health and well-being, especially for individuals who have diabetes. Poor sleep quality can have an effect on how our bodies process glucose and utilize insulin potentially resulting in diabetes related issues and complications. Additionally, we explore interventions that have the potential to improve both sleep quality and overall diabetes outcomes. Through this review it is indicated that inadequate sleep quality can influence glucose control, increase the risk of complications associated with diabetes and reduce quality of life. Furthermore, we’ve identified interventions that show promise in improving both sleep quality and overall outcomes for individuals with diabetes. These interventions include implementing lifestyle changes, making modifications utilizing behavioral therapies and incorporating device-based strategies. We suggest that future studies use experimental designs and objective measures of sleep quality and glucose metabolism and include diverse samples of different types of diabetes.